Phytochemistry, quality control and medicinal uses of Saffron (Crocus sativus L.): an updated review - Aissa, Rabha; Ibourki, Mohamed; Ait Bouzid, Hasna; Bijla, Laila; Oubannin, Samira; El Hassan, Sakar; Jadouali, Simohamed; Hermansyah, Andi; Goh, Khang Wen; Long, Chiau Ming *; Bouyahya, Abdelhakim; Gharby, Said (Jurnalul Pentru Medicina Si Viata S.R.L., 2023)
Saffron, botanically known as Crocus sativus L., is renowned as the world's most expensive spice and has been utilized in various fields since ancient times. Extensive scientific research has been conducted on Crocus sativus (C. sativus), focusing on its phytochemical composition, diverse applications, and biological activities. C. sativus phytochemicals consist mainly of three compounds, namely crocin, picrocrocin, and safranal, which are responsible for most of its properties. Saffron is rich in bioactive compounds, more than 150 of which have been isolated. Owing to its unique composition and properties, saffron is used in various fields, such as the food industry, perfumery, cosmetics, pharmaceutics, and medicine. However, the high economic value of saffron makes it susceptible to adulteration and various fraudulent practices. To deal with this issue, a number of methods and techniques have been developed to authenticate and determine adulterants in saffron. This paper presents a bibliometric study of saffron based on the Web of Science database, analyzing 3,735 studies published between 2000 and 2021. The study also examined author participation and collaboration networks among countries. Production, transformation, chemical composition, methods of adulteration detection, uses, and health properties of saffron are also discussed.